MiR-6803-5p Promotes Cancer Cell Proliferation and Invasion via PTPRO/NF-κB Axis in Colorectal Cancer - Yan, Shushan; Cheng, Min; Duan, Quanhong; Wang, Zengfang; Gao, Wenfeng; Ren, Bin; Xu, Donghua (Mediators of Inflammation, 2019)
Accumulated studies have implicated microRNAs (miRNAs) exert modifying effects on colorectal cancer (CRC). Protein tyrosine phosphatase, receptor type O (PTPRO) has been identified as a tumor suppressor in several kinds of cancer, including CRC. Previously, we have found that exosome-encapsulated miR-6803-5p is increased in CRC. However, the mechanism of miR-6803-5p in CRC is not clear yet. This study is aimed at elucidating the effect of miR-6803-5p in colorectal carcinogenesis. Expression of miR-6803-5p and PTPRO mRNA in peripheral blood mononuclear cells of CRC patients is estimated by real-time PCR. PTPRO protein in CRC cells is detected by western blot. To verify the association of miR-6803-5p with PTPRO, luciferase reporter assay is performed. CCK-8 and EdU assays are conducted to assess cell proliferation. Real-time PCR and ELISA are applied to detect cytokine expression in CRC cells. Cell invasion and migration assays are evaluated by transwell and scratch tests. Immunofluorescence is carried out to determine the activation of NF-κB in HCT116 cells. Negative correlation is demonstrated between miR-6803-5p and PTPRO in CRC. PTPRO is demonstrated to be a direct target of miR-6803-5p. miR-6803-5p can promote cancer cell proliferation and invasion and enhance inflammation through PTPRO/NF-κB axis in CRC, which serves as a useful target for CRC.